Incidencia de los métodos activos en el proceso enseñanza-aprendizaje en la modalidad de estudios a distancia, de la unidad educativa experimental fisco misional José María Vélaz, (IRFEYAL) extensión Piñas, del cantón Piñas, provincia de El Oro, en el período 2010–2011. Lineamientos alternativos - Tapia Espinosa, Lusmila Carmita (2014)
We should note that today the methods and procedures of the teaching - learning activity proposed in the faculty and student participation, have raised several responses that seek to change and modify the practice of teaching and student learning. Therefore, the present research was aimed to determine the incidence of active methods in the process of teaching and learning at a distance, of the Education Unit Experimental Treasury Missionary José María Vélaz (IRFEYAL) cantón Piñas province of El Oro in the 2010-2011 period and propose alternative guidelines to overcome the problems identified through research. The methodology allowed to find the most appropriate way for the development of this work, the methods used were : scientific , inductive, deductive , and descriptive that guided the research process and as the survey techniques aimed at teachers and students of the unit used Experimental educational Missionary Treasury Vélaz José María (IRFEYAL) collect information that allowed for interpretation and thus reach conclusions that enhance the teaching-learning process in the college being studied. After the analysis and interpretation of results and corresponding discussion concluded that the methodology of distance education was not properly applied prevailing traditional conceptions of education in curriculum design, content, study guides, among others. However we should note that despite the diversity of responses that include active methods, you have to orient the student to the importance of the correct application of these methods to help improve the teaching-learning process. Finally alternative guidelines are established for the purpose of the methods that will be developed in the concept of learning is treated as an active process that puts the creation and recreation of knowledge with which the student account , seeking to contribute to solve the problems identified . This will be done through the exchange of ideas, opinions, solutions to the different group of tasks and activities mostly on the experiences of teachers and students.